Word Processor and Word Processing Role for Online Business - Juliana, Tri Sukardi (International Research Journal of Management, IT & Social Sciences, 2015)
This article was intended to describe the role of word processor and word processing for business. Word processor is software specifically designed to process the data. With the word processor, its very easy for people to do the work or making important documents. Word processor to function in the world of education, government, medicine and others. The human need for data generation is so important. This is evident from the number of people using Microsoft Word or a word processor to create documents. Even these days almost all people in desperate need of data processing applications, because with this application everybody can be facilitated in making important documents or create a story, papers, letters and others.